2020
DOI: 10.1161/strokeaha.120.029628
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Cardiac Troponin T for Risk Stratification in Patients With Embolic Stroke of Undetermined Source

Abstract: Background and Purpose: Optimal secondary prevention for patients with embolic stroke of undetermined source (ESUS) remains unknown. We aimed to assess whether high-sensitivity cardiac troponin T (hs-cTnT) levels are associated with major vascular events and whether hs-cTnT may identify patients who benefit from anticoagulation following ESUS. Methods: Data were obtained from the biomarker substudy of the NAVIGATE ESUS trial, a randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
15
1
3
Order By: Relevance
“…This is the first real-world cohort study on troponin levels in ESUS and validates the finding of a recent clinical trial substudy that the troponin level is a predictor of the risk of vascular events in patients with ESUS [ 5 ]. There is an urgent need to identify prognostic biomarkers related to potential cardiac dysfunction after ESUS [ 1 ].…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This is the first real-world cohort study on troponin levels in ESUS and validates the finding of a recent clinical trial substudy that the troponin level is a predictor of the risk of vascular events in patients with ESUS [ 5 ]. There is an urgent need to identify prognostic biomarkers related to potential cardiac dysfunction after ESUS [ 1 ].…”
supporting
confidence: 81%
“…Recent studies have suggested that elevated cTn levels are more common in patients with ESUS than in those with noncardioembolic stroke [ 3 ]. Elevated cTn levels may be associated with worse clinical outcomes and a higher risk of vascular events after stroke [ 4 , 5 ]. Therefore, we investigated the effectiveness of conventional cTn I (cTnI) and high-sensitivity cTn T (hs-cTnT) levels in predicting clinical outcomes in patients with ESUS.…”
mentioning
confidence: 99%
“…However, a most recent substudy of the NAVIGATE-ESUS trial showed that high-sensitivity cardiac troponin T (hs-cTnT) was associated with increased rates of cardiovascular event but did not find any evidence supporting anticoagulation in these patients. This indicates that hs-cTnT is not useful to guide management of anticoagulation (76). Only limited evidence exists for the association of CK-MB with cardioembolism hindering any firm conclusions yet (41,77).…”
Section: Blood-based Biomarkers Of Myocardial Stressmentioning
confidence: 99%
“…29 Further, in patients with embolic stroke of undetermined source, elevated cTn was associated with an increased risk for cardiovascular events. 30 Moreover, elevated hs-cTn was linked with more severe matter lesions of the brain, suggesting silent brain infarction as one possible link. 31 This silent brain damage of the white matter may well go along with dementia.…”
Section: Prognosismentioning
confidence: 99%